2012
DOI: 10.1021/nl300741h
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Electrical Properties of VO2 Nanobeams Using an Ionic Liquid as a Gating Medium

Abstract: Vanadium dioxide (VO(2)) is a strongly correlated transition metal oxide with a dramatic metal-insulator transition at 67 °C. Researchers have long been interested in manipulating this transition via the field effect. Here we report attempts to modulate this transition in single-crystal VO(2) nanowires via electrochemical gating using ionic liquids. Stray water contamination in the ionic liquid leads to large, slow, hysteretic conductance responses to changes in the gate potential, allowing tuning of the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
178
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(185 citation statements)
references
References 23 publications
6
178
0
1
Order By: Relevance
“…However, it is often difficult to achieve such high electric fields by conventional dielectric gates. 1,2 Recently, extra-high electric fields are achieved by approaches such as Schottky junctions, 3,4 polar adsorbates 5,6 or ionic liquids [7][8][9][10][11][12] as dielectric gates in field-effect transistor devices. 13,14 For example, Xu et al 15 studied the modulation of grain boundary barriers in ZnMgO/ZnO/sapphire heterostructure by DI water and they found that the electronic conduction property of ZnO layer far beneath the surface could be switched from Ohmic to Schottky junction.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to achieve such high electric fields by conventional dielectric gates. 1,2 Recently, extra-high electric fields are achieved by approaches such as Schottky junctions, 3,4 polar adsorbates 5,6 or ionic liquids [7][8][9][10][11][12] as dielectric gates in field-effect transistor devices. 13,14 For example, Xu et al 15 studied the modulation of grain boundary barriers in ZnMgO/ZnO/sapphire heterostructure by DI water and they found that the electronic conduction property of ZnO layer far beneath the surface could be switched from Ohmic to Schottky junction.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In addition, this material has attracted much attention for its potential applications in ultrafast optical and electrical switching. [9][10][11][12][13] Therefore, much effort has been made to modulate the MIT by various approaches such as strain engineering, 14,15 ionic liquid gating, [16][17][18] electric field-induced oxygen vacancy, 19 and chemical doping. [20][21][22][23][24][25] In terms of chemical doping, using metal elements such as tungsten during growth can dramatically change the transition properties 20,26 , but it is an irreversible process.…”
mentioning
confidence: 99%
“…[19][20][21][22] According to Ji et al, 19 stray water in an IL gate induces large, slow, and hysteretic conductance modulation under applying gate bias. This operation allows tuning of the activation energy and changes conductance by an order of magnitude, resulting in hydrogen doping through the electrochemical reaction of water.…”
Section: Overview Of Electrochemical Transistorsmentioning
confidence: 99%
“…10,15 All of these methods require a high temperature of at least 150 • C. Recently, electric fields have been used for both hydrogenation and oxidation of oxides at room temperature. 16,[19][20][21] For example, a strong electric field in an ionic liquid (IL) gate induces oxygen vacancy formation 042303-2 T. Kanki and H. Tanaka APL Mater. 5, 042303 (2017) in VO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation